Synthesis and characterization of the nido-platinaborane 7,7-(PPh3)2-7-PtB10H11-11-OC(O)Me - Miao, Jinling; Nie, Yong; Chen, Haiyan; Wang, Daqi; Enders, Markus; Siebert, Walter; Sun, Guoxin; Dou, Jianmin (Zeitschrift für Naturforschung. B, a journal of chemical sciences, 2011)
The reaction of closo-B 10 H 10 2− with PtCl 2 (PPh 3 ) 2 in the presence of MeCOSH afforded the title platinaborane nido-7,7-(PPh 3 ) 2 -7-PtB 10 H 11 -11-OC(O)Me (1), which has been characterized by IR and NMR spectroscopy, MS, elemental analysis, and single-crystal X-ray diffraction. In contrast to the known products having exo-polyhedral Pt-S-C-O-B ring(s) from the same reaction with Ph- COSH, compound 1 has a B-acetoxy group on the open PtB 4 face of the nido-PtB 10 cluster. The structure of 1 features both intramolecular/intermolecular C-H· · ·O hydrogen bonds and intramolecular C-H· · ·H-B dihydrogen bonds, which link the molecules into a 1-D chain structure. Graphical Abstract Synthesis and Characterization of the nido-Platinaborane 7,7-(PPh3)2-7-PtB 10 H 11 -11-OC(O)Me
Elektronische Reproduktion der Druckausgabe
Im Titel sind die Zahlen 3, 2, 10 und 11 tiefgestellt
Gesehen am 19.08.2022